Evaluation of the Thermophysical, Sensory, and Microstructural Properties of Colombian Coastal Carimañola Obtained by Atmospheric and Vacuum Frying - Diofanor Acevedo C.; Piedad M. Montero; Jhon Rodriguez Meza; R. Sandrith Sampayo; Raul Jose Martelo (International Journal of Food Science)
The quality of fried products affects consumer purchase decisions, and frying is an important stage in the production process. The objective of this research was to evaluate the thermophysical properties, the sensory quality, and microstructure of Colombian coastal Carimañola traditionally manufactured, in atmospheric frying and vacuum frying conditions. Lower moisture and fat content were reported in samples fried under vacuum compared to samples fried under atmospheric conditions, which is associated with the vacuum pressure during the process. Thermophysical properties, related to heat transfer in the samples, showed a correlation between thermal conductivity and moisture content. The micrographs visualized the changes in the porous structure of the coastal Carimañola. A greater effect was evidenced in the samples obtained by atmospheric frying because higher temperatures were used. The sensory evaluation reflected a preference for Carimañolas made with conventional frying. This research provides a basis for consumer purchases of traditionally fried products made with vacuum frying.